The Growth and Yield of Sweet Corn Fertilized by Dairy Cattle Effluents Without Chemical Fertilizers in Inceptisols - Yudi Sastro; Indarti Puji Lestari (JOURNAL OF TROPICAL SOILS, 2011)
Several research has proven the role of dairy cattle effluents in improving the growth and yield of some crops. However, its role in supporting the growth and yield of sweet corn, especialy in Inceptisols, has not been reported. The study aims to determine the effect of dairy cattle effluents on growth and yield of sweet corn in Inceptisols. The pot study was conducted in a greenhouse of the Assessment Institute for Agriculture Technology of Jakarta. The treatments were fertilization using dairy cattle effluents (without dilution, dilution with water 1:1 and 1:2), a mixtureof Urea, SP-36 and KCl (NPK), and without fertilizer. The experimental design was a completely randomized design with five replications. Compared to a without fertilizer treatment, dairy cattle effluents were significantly increased plant height (114%), leaf number (136%), cob weight (131%), cob length (124%), and cob diameters (128%). Base on cob weight, relative agronomic effectiveness (RAE) of dairy cattle effluents reached 38.4% (without dilution), 47.5% (dilution with water 1:1), and 62.1% (dilution with water 1:2).Keywords: Dairy cattle effluents, fertilizer, sweet corn